Efecto del sustrato y la exposición a la luz en la producción de una cepa de Trichoderma sp. - Mónica Chávez-Garcia; José Salvador Montaña-Lara; María Mercedes Martínez-Salgado; Marcela Mercado-Reyes; María Ximena Rodríguez; Balkys Quevedo-Hidalgo (Universitas Scientiarum)
Effects of substrate and light exposition in the production of Trichoderma sp. In order to evaluate the effect of temperature and lightconditions on biomass production of a Trichoderma sp. strain, three culture media were tested: rice 53% (w/w), rice 53% (w/w) -molasses3% (w/w) and rice 53% (w/w)-molasses 10% (w/w) in distilled water. Incubation conditions were: 25°C, constant light and a photoperiodof 24 h light/24 h darkness during 8 days. The evaluated parameters were population density (conidia/mL), spore germination after 24 hoursand purity percentage. The results showed that solid fermentation using rice - distilled water as substrate at 25°C and constant light, allowedthe highest conidia yield (45x1018 conidia/mL), 96% germination after 24 hours, and 92.1% purity. The liquid fermentation rendered a purityof 76.8% and conidia germination of 91.2% after 24 hours, showing a disadvantageous lower purity percentage compared to solidfermentation.